1999
DOI: 10.1021/bi9820917
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Paracoccus denitrificans Electron Transfer Flavoprotein:  Structural and Electrostatic Analysis of a Conserved Flavin Binding Domain,

Abstract: The crystal structure of electron transfer flavoprotein (ETF) from Paracoccus denitrificans was determined and refined to an R-factor of 19.3% at 2.6 A resolution. The overall fold is identical to that of the human enzyme, with the exception of a single loop region. Like the human structure, the structure of the P. denitrificans ETF is comprised of three distinct domains, two contributed by the alpha-subunit and the third from the beta-subunit. Close analysis of the structure reveals that the loop containing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
73
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 35 publications
7
73
0
Order By: Relevance
“…Etf proteins are heterodimers of EtfA and EtfB and contain noncovalently bound flavin adenine dinucleotide (FAD). The crystal structure of EtfA of Paracoccus denitrificans was solved, and the FAD binding site was identified in the structure in the conserved C terminus (44,45). The Q240, V241, Q243, T244, Q263, and H264 residues that interact with the isoalloxazine ring of the FAD in P. denitrificans are fully conserved in EtfA Aw .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Etf proteins are heterodimers of EtfA and EtfB and contain noncovalently bound flavin adenine dinucleotide (FAD). The crystal structure of EtfA of Paracoccus denitrificans was solved, and the FAD binding site was identified in the structure in the conserved C terminus (44,45). The Q240, V241, Q243, T244, Q263, and H264 residues that interact with the isoalloxazine ring of the FAD in P. denitrificans are fully conserved in EtfA Aw .…”
Section: Resultsmentioning
confidence: 99%
“…FAD's ribityl and ADP moiety is coordinated by 10 additional residues, 6 of which (S226, R227, S259, N278, K279, and D296) are also conserved in EtfA Aw . EtfB contains the binding site for a second cofactor, AMP (44,45). Two of the residues shown to be involved in AMP binding (G120 and A123 in P. denitrificans) are also conserved in EtfB Aw .…”
Section: Resultsmentioning
confidence: 99%
“…Simulated X-ray Scattering Profiles-The x-ray structures of human and P. denitrificans ETFs have been solved previously (14,15). Using these atomic coordinates, simulated x-ray scattering profiles were generated for solvated structures of both human and P. denitrificans ETFs and fitted against the experimental data for each protein, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic and redox properties of the two proteins are very similar (12,13). Crystal structures have been determined for both ETFs at resolutions of 2.1 and 2.6 Å, respectively (14,15). These reveal that the overall fold for both proteins is identical with the exception of a single loop region.…”
mentioning
confidence: 92%
“…All ETFs possess one equivalent of non-covalently bound FAD per ETF heterodimer, except the ETF from Megasphaera elsdenii, which contains 2 equivalents of FAD per dimer (8). It has been shown that AMP (1 equivalent) is associated with the housekeeping ETFs from pigs (9), humans (10), and Paracoccus denitrificans (11) and with the specialized ETF from Methylophilus methylotrophus (12).…”
mentioning
confidence: 99%